Evaluation of Palatal Rugae in Patients for Maxillary Dental Prostheses: Palatal Rugae in Patients for Maxillary Dental Prostheses - Khan, Sartaj; Raza, Muhammad; Tahir, Maryam; Manzar, Samia (Pakistan Journal of Health Sciences, 2022)
Significance and importance of palatal soft tissue rugae increases many folds when replacement of missing maxillary teeth with conventional complete denture is part of treatment plane. Objectives: To quantify the shape and size of rugae in completely and partial edentulous arches in both males and females. Methods: A total of 200 patients were selected on the basis of inclusion and exclusion criteria and after obtaining informed consent, impression with Alginate impression material were made and poured to form dental casts. Pattern and shapes of rugae were delineated with graphite marker. Under a good source of light different shapes, thus outlined, were counted in number and measured in length, categorizing them in various shapes such as divergent, wavy, curved and straight. Age, arches were computed for frequency and measuring the mean with standard deviation. All data were computed by using SPSS (version 22). Results: Out of 200 patients, a male (n=89) to female (n=111) ratio of 0.80 was found with a mean age of 52.6 and standard deviation of 11.3. Partially edentulous cases were 51%, while the rest were completely edentulous. A total of 1367 rugae were found in both types of patients. Females had more number of rugae (n=773) than males (n=594). Similarly primary rugae were higher in numbers (n=1132) than secondary rugae (n=235) and the observed difference was statistically significant (p=0.001). Conclusions: It was concluded in this study that female and partially edentulous arches had more numbers of rugae as compared to males and completely edentulous arches respectively.